2016
DOI: 10.22146/ijbiotech.15283
|View full text |Cite
|
Sign up to set email alerts
|

Formulation of Medium Viscosity Chitosan-Pectin –MJ Protein Nanoparticles Conjugated with Anti-Ep-CAM and Its Cytotoxicity Against T47D Breast Cancer Cell Lines

Abstract: Chitosan nanoparticle could become potential formula to protect protein degradation during therapy,since chitosan nanoparticles have “proton sponge hypothesis” mechanism on its protection. Chitosan and pectinis used as basic formula of drug delivery because of its biodegradable and biocompatible properties. Chitosanpectin nanoparticles can be formulated by polyelectrolit complex. EpCAM showed excessive expression inepithelial cancer cells thus can be used as a therapeutic biomarker. MJ protein, a Ribosome-Inac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 17 publications
1
0
0
Order By: Relevance
“…Previous work indicated that nanoparticle designed from low chain chitosan and high methylated pectin showed good potential for improving unpurified RIP MJ activity against MCF7 breast cancer cell-line [10]. A similar result was also found from unpurified RIP MJ nanoparticle formulated by medium chain chitosan and high methylated as well as low chained chitosan and alginate [11,12]. Therefore, in this research, we explored the use of another formula using low chain chitosan and low methylated pectin as a delivery system for RIP MJ-C, a purified acidic RIP MJ protein.…”
Section: Introductionsupporting
confidence: 72%
“…Previous work indicated that nanoparticle designed from low chain chitosan and high methylated pectin showed good potential for improving unpurified RIP MJ activity against MCF7 breast cancer cell-line [10]. A similar result was also found from unpurified RIP MJ nanoparticle formulated by medium chain chitosan and high methylated as well as low chained chitosan and alginate [11,12]. Therefore, in this research, we explored the use of another formula using low chain chitosan and low methylated pectin as a delivery system for RIP MJ-C, a purified acidic RIP MJ protein.…”
Section: Introductionsupporting
confidence: 72%